Kinetic evaluation of the dehydration of Yb(III) Lu(III) and Y(III) 4-chlorobenzylidenepyruvate by thermogravimetry (TG) - Fernandes, Nedja Suely; de Araujo, Antônio Souza; Ionashiro, Massao (Eclética Química, 2006)
The dehydration kinetic of Yb, Lu and Y 4-chlorobenzylidenepyruvate was studied by using thermogravimetry and the kinetics parameters obtained by Flynn and Wall method suggest that the dehydration step follows a first order mechanism. The activation energies calculated were 103.6, 96.6 and 97.2 kJ/mol and the lifetime considering the temperature of 31 and 101 o C for the dehy- dration of these compounds were 23, 26, 31 minutes and 0.6, 1.3 and 1.4 seconds, respectively. The results have similar values and suggest that the water is attached in the same way.